COMPARATIVE ANALYSIS OF LIFESTYLE AND PURCHASING DECISIONS ON THE SHOPEE MARKETPLACE: A STUDY OF MALANGKUCECWARA COLLEGE STUDENTS - Nunung Nurastuti Utami (Bajang Institute, 2026)
This study aims to analyze differences in lifestyle and purchasing decisions on the Shopee marketplace between male and female students. Using an independent sample t-test, the results of the t-values ​​on lifestyle and purchasing decisions between male and female students were 1.116 (sig: 0.27) and -2.780 (sig: 0.007), respectively. This indicates that there is no difference in lifestyle between male and female students, but there is a difference in purchasing decisions on the Shopee marketplace between male and female students.Based on the research findings, it is recommended that lifestyle policies should not be treated differently; however, to improve purchasing decisions, a specific strategy for student purchases is needed. Further research is needed to examine factors related to the lifestyle and purchasing decisions of male and female students using different analysis methods.